2022
DOI: 10.1038/s41467-022-28004-5
|View full text |Cite
|
Sign up to set email alerts
|

Regional trade agreement burdens global carbon emissions mitigation

Abstract: Regional trade agreements (RTAs) have been widely adopted to facilitate international trade and cross-border investment and promote economic development. However, ex ante measurements of the environmental effects of RTAs to date have not been well conducted. Here, we estimate the CO2 emissions burdens of the Regional Comprehensive Economic Partnership (RCEP) after evaluating its economic effects. We find that trade among RCEP member countries will increase significantly and economic output will expand with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 68 publications
1
30
0
Order By: Relevance
“…At present, environmental regulations and laws in India are still dominated by the polluter-pays principle . However, considering pollution transfer along the supply chains, the Indian government would re-allocate export-related emission responsibility between consumers and producers to provide a basis for the establishment of intranational air pollution responsibility-sharing and pollution compensation mechanism. Major producing regions like Madhya Pradesh and West Bengal could select more friendly trading partners to avoid sacrificing residents’ health in exchange for economic gains, while consuming regions can provide appropriate environmental compensation payments and best-available technologies for producing regions .…”
Section: Discussionmentioning
confidence: 99%
“…At present, environmental regulations and laws in India are still dominated by the polluter-pays principle . However, considering pollution transfer along the supply chains, the Indian government would re-allocate export-related emission responsibility between consumers and producers to provide a basis for the establishment of intranational air pollution responsibility-sharing and pollution compensation mechanism. Major producing regions like Madhya Pradesh and West Bengal could select more friendly trading partners to avoid sacrificing residents’ health in exchange for economic gains, while consuming regions can provide appropriate environmental compensation payments and best-available technologies for producing regions .…”
Section: Discussionmentioning
confidence: 99%
“…For example, regional trade agreements, following WTO rules, are committed to employing zero or close to zero tariffs among members. Tian et al (2022) showed that complete tariff elimination among the Regional Comprehensive Economic Partnership (RCEP) members would increase the yearly global CO 2 emissions from fuel combustion by about 3.1 percent, doubling the annual average growth rate of global CO 2 emissions in the last decade. In this sense, inclusive policies such as expanding green product lists and promoting trade facilitation are urgently needed for balancing trade gains and environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…With the reduction in regional tariffs, the CO 2 emissions embodied in the trade of developing countries will surge [19]. Wang and Yang [20] investigated CO 2 emissions embodied in Chinese-Indian trade and proposed that China was a net exporter of CO 2 and a net exporter of trade.…”
Section: Introduction 1backgroundmentioning
confidence: 99%